On distortions of the transfinite diameter of disk image - Salimov, R.; Vyhivska, L.; Klishchuk, B. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.54, 517.12We investigate the so-called ring $Q$-homeomorphisms with respect to the $p$-modulus for $p>2$ on a complex plane. In particular, we establish a lower bound for the distortion of the transfinite diameter of disk image. Moreover, we solve the problem of minimization of the  functional of distortion of the transfinite diameter of a disk in a certain class of ring $Q$-homeomorphisms with respect to the $p$-modulus.